Livestreaming and Consumer Engagement in Generation Z - Satavetin, Jerapa; Sri-sumang, Supalux; Akkawanitcha, Chuanchuen; Jaroensombut, Lertlak; Kamsirimongkol, Tippawan (RATANABUTH JOURNAL, 2026)
Livestreaming has become a strategically important digital communication tool that transforms how firms interact with consumers and create business value. Unlike traditional digital media, livestreaming enables real-time interaction, heightened social presence, and personalized communication, making it especially relevant for Generation Z consumers. This article examines livestreaming from both managerial and theoretical perspectives by integrating Media Richness Theory, Social Presence Theory, the Theory of Media Synchronicity, and Consumer Engagement Theory to explain how livestreaming influences consumer engagement and business performance. A conceptual framework is proposed that illustrates how livestream interactivity builds trust through parasocial interaction and source credibility, enhances multidimensional consumer engagement, and leads to improved performance outcomes moderated by contextual factors such as product type and platform characteristics. The article also addresses the potential dark side of livestreaming, including information overload and consumer vulnerability, and offers practical implications for managers alongside specific directions for future empirical research related to Generation Z markets.